Practical Linux system administration a guide to installation, configuration, and management - Hess, Kenneth (O'Reilly, 2023)
This essential guide covers all aspects of Linux system administration, from user maintenance, backups, filesystem housekeeping, storage management, and network setup to hardware and software troubleshooting and some application management. It's both a practical daily reference manual for sysadmins and IT pros and a handy study guide for those taking Linux certification exams